Self-governing through Cultural Production in Diaspora-centric Space: A Comparative Study of Kurdistan’s Jews in Jerusalem and the Kurdish Diaspora in Berlin - Dag, Veysi (Journal of Ethnic and Cultural Studies, 2024)
This study examines how the self-organized social formations of Kurdistan’s Jews in Jerusalem and the non-Jewish Kurdish diaspora in Berlin engage in self-governing cultural production practices that they establish to regulate their communities’ cultural, emotional, and social affairs, address their challenges, and meet their objectives. The paper further analyzes the impact of cultural production on communities’ everyday lives. Specifically, self-organized social establishments embrace cultural production objects, including ethnic food, circle dances, music, and religious melodies, to stimulate cultural spaces in which community members interpret and consume cultural production’s symbolic meanings for a variety of objectives. These include, but are not limited to, the restoration of lived or ancestors’ narrated memories, the promotion of collective identities, and a sense of belonging. They also foster community formation and social cohesion, seek to surmount social and structural obstacles in their integration process, and advocate for their homeland-related politics and interests. However, these meanings and their consumption within both communities vary depending on their homeland ties and needs, barriers, and political conditions in new environments. Kurdistan’s Jewish initiatives capitalize on cultural production as a dynamic vehicle to reconstruct ancestral identities, evoke a sense of belonging, preserve ancestors’ cultural heritage, reconnect with their ancestral roots, and promote social cohesion. However, non-Jewish Kurdish diaspora establishments in Berlin harness cultural production as a sociopolitical strategy to maintain the Kurdish identity, address refugees’ integration difficulties, form their cohesive and political community, and engage in homeland politics. My findings, based on ethnographic fieldwork, 87 in-depth interviews with cultural actors and community members in Jerusalem and Berlin, and participant observations over a seventeen-month period, illustrate how self-organized formations play a vital role in the self-governing cultural production process and how they impact their communities’ affairs, challenges, and objectives.